Tristes tópicos sobre el turista inocente - Ros, Fernando Antonio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this paper I present a theoretical reflection of modern mass tourism from an anthropological viewpoint. My intention here is to outline a methodological proposal for the analysis of the effect of tourism, recovering and articulating some classical concepts of the American anthropological heritage, suitably updated. Such concepts include acculturation, cultural change and diffusion, applied to the specific problems of mass tourism and its effects. Moreover, I also examine the methodological appropriateness of applying an ethnohistorical approach in the study of the processes of socio-cultural changes brought by tourism.